A planning framework for bunker risk management : bunker adjustment factor in bunker risk management integrated framework - He, Qin. (2013)
An integrated framework has been set up to link the three risk management tools into one system. The three tools are network planning, hedging and Bunker Adjustment Factor (BAF). The focus of this report is, from the perspective of BAF, to mitigate bunker risks, with the incorporation of the other two risk management tools. However, current BAF has been accused of ‘opaque number’ by shippers, and also proved by several academic researchers to be revenue-making rather than cost recovery. In the integrated framework, bunker surcharge is aimed to be fair and transparent, so a new BAF formula would be derived from Transpacific Stabilization Agreement (TSA) and Maersk SBF formulae. In order to demonstrate the advantages of the new formula, comparisons would be done between Maersk SBF and the new formula in numerical results. The Excel application of the integrated model adds to the merits of the bunker surcharge result, which overall gives a more reliable and transparent surcharge. The survey and interview results would be used to evaluate the integrated model about its short-term, long-term benefits and possible problems encountered. Accordingly, recommendations would be made to the current industrial practices of bunker risk management. Future studies suggest improvements in BAF policy of the integrated framework, which is related to the determination of bunker base price.